ZUR CHRONOLOGIE DER MENIPPEEN DES VARRO - Krenkel, Werner (Myrtia, 1996)
The author of this article analyzes three fragments of Varro’s Menippean Satires (Frg. 183, 334 and 104 Buecheler) which are supposed to contain further information about the dating of these lines. From the interpretation of these fragments he tries to establish more precisely their chronology.